Effect of Grain Shape on Texture Formation during Severe Plastic Deformation of Pure Copper1 . Issue 4 (17th March 2017) - Jahedi, Mohammad; Beyerlein, Irene J.; Paydar, Mohammad Hossein; Knezevic, Marko
Abstract : In this study, the authors use a combination of electron backscattered diffraction and polycrystal plasticity modeling to study the effect of grain shape on texture development in high pressure torsion and high pressure double torsion in high purity Cu. With varying applied pressures and after a large amount of strain corresponding to two to four turns, the average aspect ratios of the grains has changed from being elongated under higher pressures to nearly equiaxed for lower pressures, while keeping the average grain size similar among all samples analyzed. Polycrystal modeling is used to help isolating the deformation effect from the grain shape effect. The authors show that grains with elongated shapes form shear textures with a predominant C component, whereas those with largely equiaxed grains possess conventional shear textures. Abstract : Analysis performed using electron backscattered diffraction and polycrystal plasticity modeling of microstructure evolution in high purity polycrystalline copper during severe plastic deformation demonstrates that grains with elongated shapes form shear textures with a predominant C texture component, whereas those with largely equiaxed grains possess conventional shear textures.